The Diary of Samuel Pepys - Pepys, Samuel, 1633-1703; Braybrooke, Richard Griffin, Baron, 1783-1858 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Diary of Samuel Pepys" by Samuel Pepys is a historical account written during the mid-17th century. The work revolves around the detailed and personal diary entries of Samuel Pepys, chronicling a decade of significant historical events, including the Restoration of the monarchy, the Great Plague, and the Great Fire of London, while also providing insight into the social and political life of the time through Pepys's unique perspective. The opening of the diary begins with Pepys reflecting on his good health at the start of 1659-60, followed by a snapshot of the political landscape in England, specifically the turmoil related to the Rump Parliament and various military figures. He describes his daily life, social engagements, and the dynamics at play in the government, showcasing the intricate relationship between public duty and personal experience. Notable figures such as Lord Lambert and General Monk are mentioned, highlighting the tension between different factions within the political sphere. Throughout this introductory portion, Pepys's wit and vivid observations lay the groundwork for a fascinating glimpse into the life and times of a pivotal era in British history. (This is an automatically generated summary.)
Release date is 2002-07-01
This etext was produced by John Hill
Keywords: Pepys, Samuel, 1633-1703 -- Diaries; Cabinet officers -- Great Britain -- Diaries; Diarists -- Great Britain -- Diaries; Great Britain -- Social life and customs -- 17th century -- Sources; Great Britain -- History -- Charles II, 1660-1685 -- Sources